2022
DOI: 10.1155/2022/6425121
|View full text |Cite
|
Sign up to set email alerts
|

Ruscogenin Ameliorated Sjögren’s Syndrome by Inhibiting NLRP3 Inflammasome Activation

Abstract: This article investigated the role and the specific mechanism of Ruscogenin in Sjögren's syndrome (SS). NOD/ShiLtJ mice were treated with Ruscogenin, and acinar cells isolated from submandibular glands were treated with TNF-α, Ruscogenin and transfected with NLRP3 overexpression plasmid. Salivary flow rate (SFR) was measured at weeks 11, 13, 15, 17, and 20. Histological analysis of the submandibular glands was conducted by hematoxylin-eosin staining assay. IL-6, IL-17, TNF-α, and IL-1β mRNA expression was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Ruscogenin, as a natural compound, has been previously reported to suppress NLRP3 inflammasome activation in autoimmune disease and ischemic injury (Cao et al, 2016, He et al, 2022. In our study, we found that Ruscogenin effectively inhibited E protein-induced pyroptosis via downregulating NLRP3 expression, and this effect may be linked to NF-κB inhibition.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Ruscogenin, as a natural compound, has been previously reported to suppress NLRP3 inflammasome activation in autoimmune disease and ischemic injury (Cao et al, 2016, He et al, 2022. In our study, we found that Ruscogenin effectively inhibited E protein-induced pyroptosis via downregulating NLRP3 expression, and this effect may be linked to NF-κB inhibition.…”
Section: Discussionsupporting
confidence: 65%
“…Ruscogenin, as a natural compound, has been reported to suppress NLRP3 inflammasome activation in autoimmune disease and ischemic injury (Cao et al, 2016, He et al, 2022. To investigate whether Ruscogenin could alleviate E protein-induced THP-1 pyroptosis, THP-1 was pre-treated with various concentrations of Ruscogenin for 1 h followed by stimulation with 1 μg/ml of E protein.…”
Section: Ruscogenin Reversed Sars-cov-2 E Protein-induced Pyroptosismentioning
confidence: 99%
“…8-10 NLRP3 overexpression could reverse the up-regulation of pro-apoptotic factor (Bax) and the downregulation of anti-apoptotic factor (Bcl-2) in acinar cells. 28 Anfibatide could inhibit the expression of NLRP3, ASC, cleaved-caspase-1, Bax and cleaved-caspase-3, promoted the expression of Bcl-2 in cerebral ischemia reperfusion in vivo and in vitro, which indicates that anfibatide could alleviate inflammation and apoptosis through inhibiting NF-kappaB/NLRP3 axis. 29 Alpha-mangostin exerted a protective effect on NLRP3 inflammasome-mediated apoptosis in LPS-induced NPCs through regulating NF-κB signaling.…”
Section: Discussionmentioning
confidence: 87%
“…The NLRP3 inflammasome can be activated by many activators, such as reactive oxygen species (ROS), K + channel openers, uric acid, and endotoxins, and plays an important role in insulin resistance and the pathogenesis of diabetes 8–10 . NLRP3 overexpression could reverse the up‐regulation of pro‐apoptotic factor (Bax) and the downregulation of anti‐apoptotic factor (Bcl‐2) in acinar cells 28 . Anfibatide could inhibit the expression of NLRP3, ASC, cleaved‐caspase‐1, Bax and cleaved‐caspase‐3, promoted the expression of Bcl‐2 in cerebral ischemia reperfusion in vivo and in vitro, which indicates that anfibatide could alleviate inflammation and apoptosis through inhibiting NF‐kappaB/NLRP3 axis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its use in the treatment of hemorrhoids, this substances has also been reported to have bene cial effects in the treatment of acute and chronic in ammation, prevention of blood-brain barrier dysfunction and alleviation of acute lung injury, and pulmonary arterial hypertension diseases [7]. In addition to these, it suppresses hepatocellular carcinoma metastasis, alleviates lipopolysaccharide-induced pulmonary endothelial cell apoptosis, improves Sjögren's syndrome, and alleviates particulate matter-induced acute lung injury [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%